Gene variants in pro-coagulant and anti-coagulant genes could be prognostic genetic markers of COVID-19 susceptibility. Issue 11 (November 2022) - Srivastava, Swati; Kumari, Babita; Garg, Iti; Dogra, Vikas; Ghosh, Nilanjana; Singh, Yamini; Bargotya, Mona; Bhattar, Sonali; Gupta, Utkarsh; Jain, Shruti; Hussain, Javid; Varshney, Rajeev; et al.
Abstract: Background: Present study aimed to identify DNA polymorphisms (variants) which can modulate the risk of COVID-19 infection progression to severe condition. TaqMan based SNP genotyping assay was performed for 11 single nucleotide polymorphisms (SNPs) in pro-coagulant and anti-coagulant genes. Methodology: A total of 33 COVID-19 patients, including dead, severe and moderately infected individuals were compared to 35 healthy controls. Both alleles in the SNP were labelled with two different fluorescent dyes (FAM and VIC) during assay formulation. DNA of study subjects were mixed with SNP assay and TaqMan master mix on 96 well PCR plate according to manufacturer's protocol and RT-PCR was performed. Allelic discrimination assay gave clear results for presence of specific allele in each sample. Three SNPs were located in the pro-coagulant genes, another three involved in blood clot dissolution while rest five were in the genes encoding natural anti-coagulants. COVID-19 infected patients were further sub-divided into three groups, deceased (n = 16), severe (n = 10) and moderately infected (n = 7). Results: SNP genotyping showed significant differences between COVID-19 patients and controls in two SNPs, rs6133 in Selectin-P (SELP) and rs5361 in Selectin-E (SELE) gene. Also, rs2020921 and rs8176592, in clot dissolution genes, tissue Plasminogen activator (tPA) and tissue factor pathway inhibitor (TFPI) respectively showed significant genotypic and allelic difference in patients of COVID-19 compared to healthy controls. Further three SNPs rs2227589, rs757583846, and rs121918476 in natural anti-coagulant genes anti-thrombin III (ATIII), protein C (PROC), and protein S (PROS) respectively showed statistically significant difference between the study groups. Conclusion: Our findings indicate that gene variants, those involved in coagulation and anti-coagulation may play a major role in determining individual susceptibility to COVID-19. Abstract : COVID-19; SNP; Anti-coagulants; Genotyping